2013
DOI: 10.1002/j.1532-2149.2013.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive exposure versus avoidance in patients with chronic pain: Adherence matters

Abstract: The addition of IE to behavioural exposure did not improve outcomes. However, higher adherence to either attentional strategy was associated with larger effect sizes on all measures, suggesting factors shared by the two treatments could have contributed to the outcomes. Taken as a whole, the results suggest that increasing adherence to treatment strategies, possibly by motivational measures, would improve the overall outcomes of these interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 67 publications
3
54
0
1
Order By: Relevance
“…To evaluate test-retest reliability, sensitivity to change, and convergent validity, we used a separate sample (Sample 3, n = 140) that had recently completed an intervention designed, in part, to modify self-efficacy beliefs. 41 …”
Section: Analysis Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate test-retest reliability, sensitivity to change, and convergent validity, we used a separate sample (Sample 3, n = 140) that had recently completed an intervention designed, in part, to modify self-efficacy beliefs. 41 …”
Section: Analysis Strategymentioning
confidence: 99%
“…The data employed in this study were derived from previous studies [39][40][41] at this center that had been approved by the Northern Sydney Area Human Ethics Committee. All participants provided written informed consent allowing us to use their deidentified data in this research.…”
Section: Ethical Approvalmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviews with these patients indicated that addressing loss and cultivating acceptance may be crucial before any behavior changes are initiated. Nicholas et al studied whether a behavioral exposure method that aims to reduce pain-avoidance behaviors would add benefit to standard CBT [15]. Although the results appeared to indicate that this add-on to CBT did not significantly differ from CBT alone, higher adherence in each group was once again associated with improvement on measures of pain, pain perception, disability, and depression.…”
Section: Cognitive and Behavioral Treatmentsmentioning
confidence: 99%
“…(2015) se estudió el efecto de la TCC en pacientes australianos con dolor crónico en un entorno de salud pública, a través de 5 sesiones online aplicadas a lo largo de 8 semanas, encontrándose grandes mejoras en variables como discapacidad, ansiedad, depresión y la media de dolor percibido tras el tratamiento, mejoras que fueron mantenidas en el seguimiento a los 3 meses. Además, se encontraron efectos de pequeños a moderados en otras variables de interés como la autoeficacia antes el dolor, el miedo al movimiento y la aceptación del dolor, que se han identificado como objetivos importantes en la TCC para el manejo del dolor (Nicholas et al, 2012;Nicholas et al, 2014). Por añadidura, los pacientes mostraron una elevada satisfacción con el tratamiento y una reducción del uso de medicación y de las demandas y el uso de los servicios de salud.…”
Section: Tics Y Dolor Crónicounclassified